Identification Of Appropriate Architectural Elements For Design Application In Tropical Regions Of Southeast Asia - Hilda Kamila; Erwin Djuni Winarto (International Journal of Health Engineering and Technology, 2026)
Southeast Asia with tropical regions has unique climate characteristics, such as high humidity, significant rainfall intensity throughout the year and high temperatures. These conditions require an architectural approach that is responsive to climate in order to create thermal comfort in buildings. The purpose of this study is to identify what architectural elements are considered appropriate to be applied in building design in tropical Southeast Asia. The methods used in this study include literature studies and case study analysis of several buildings designed with a tropical approach in the region. Through this approach, it is hoped that this study can provide an initial overview of architectural elements that have the potential to support adaptive designs to tropical climate conditions. The results of this study will be the basis for the development of contextual and sustainable tropical architectural designs.